Political interests and family affairs in the correspondence of Teophila née Leszczyńska Wiśniowiecka (1680–1757) - Jakuboszczak, Agnieszka; Manyś, Bernadetta (Balcanica Posnaniensia. Acta et studia, 2022)
Teofila (1680-1757) belongs to the group of active magnates living in the first half of the 18th century which, however, remains less. The preserved correspondence makes it possible to analyze her activities in the political and family fields. Her letters are therefore a valuable source of knowledge about the everyday life of her relatives and about the backstage of political events in the Polish-Lithuanian Commonwealth.